“Troy-upon-Guadalquivir: Imagining Ancient Architecture at King Alfonso XI’s Court” - Rodríguez Porto, Rosa María (Troianalexandrina, 2005)
Abstract The depictions of Troy in the Crónica Troyana de Alfonso XI (1350) —a Castilian illuminated manuscript with the Spanish version of the Roman de Troie— provide an exemplum to analyze the function of anachronism as a rhetorical device in Arts and Literature. Moreover, these urban images have an unmistakable Islamic appearance which allows us to go deeper into the comprehension of the multicultural context of the Iberian Peninsule, as well as into its singular artistic consequences.